PENGARUH KONFLIK KERJA DAN STRES KERJA TERHADAP KINERJA KARYAWAN PADA CV. APOTIK KELUARGA PEKANBARU - Putra, Eka (Eko dan Bisnis: Riau Economic and Business Review, 2020)
The purpose of this study was to analyze the effects of work conflict and work stress on employee performance CV. Apotik Keluarga Pekanbaru. This study uses descriptive and quantitative methods with a population and the sample is all employees that totaling 66 people. The average values for all Work Conflict statements and Work Stress variables are 3.00 and 3.02, respectively, which means that these two factors are in the medium class interval. The value of t_count for the work variable conflict t_count> t_table (-2.196> 1,998) and the significance of 0,000 <0.05, meaning that work conflict has a significant effect on employee performance. A negative sign indicates the higher the level of work conflict, the lower the employee's performance. As for the Work Stress variable t count <t table (-0.033 <1,998) and probability (0.974)> 0.05. So the Work Stress variable partially has no effect and is not significant on Employee Performance. Then from the simultaneous test results obtained that Fcount> Ftable (22,010> 3.14) and a probability value of 0,000 <0.05 then the variable Work Conflict and Work Stress simultaneously have a significant effect on Employee Performance CV. CV. Apotik Keluarga Pekanbaru. Based on the Adjusted R Square value obtained at 0.393 on the coefficient of determination test, the effect is 39.3%.